A growing niche: German blockchain companies - Markus Demary; Vera Demary (Institut der deutschen Wirtschaft (IW), 2021)
A growing, but still small number of companies in Germany are supplying products and services based on the blockchain technology. Most of these are start-up companies and are headquartered in Berlin. Although a lot of them are focused on providing financial services, an increasing number of blockchain companies has started developing other blockchain-based services.
Keywords: 330